Adolescência e sexualidade: vulnerabilidade às DSTS, HIV/AIDS e a gravidez em adolescentes paraibanos - Ribeiro, Karla Carolina Silveira (2011)
Based on the conception that beliefs concerning sexuality play an important role in the behavior of adolescents, it was used the Foucault‟s perspective in order to identify the characteristics and analyze the possible associations among the pregnancy in the adolescence, the STDs/AIDS, and the situations of vulnerability of adolescents who live in the state of Paraíba. The sample comprised 8.741 adolescents, been 62% female, in the age range of 12 to 20 years old (average of 16 years old), enrolled in public schools of 34 cities classified based on the demographic size according to the city social indicators. It was used a self-report structured questionnaire and the group technique of focal discussion. In order to analyze the quantitative date, it was used descriptive statistics, been used position and variability measures, besides it, it was performed bivariate tests. The analysis of the group‟s content was performed based on Categories which were determined based on the emerged themes. According to the results, three thematic categories have emerged. The first, which was denominated Sexual Practice (sub-categories: Sexual Initiation and Determinant Factors); the second was denominated Prevention (sub-categories: The Use of Condom and Contraceptive Methods); and the third category, Vulnerability to AIDS (sub-categories: Perception of Vulnerability and Information). Concerning to the Sexual Practice, 2.732 participants declared have an active sexual life (31%), with initiation in 15,6 years old to the women and 14,6 years old to men, with significant statistical difference in relation to the sex (64% male p < 0,001) and the size of the cities (minor indices in medium size cities). The differentiation of gender was also obtained in relation to the first sexual partner, mainly related to the age (average of 21 years old to women and 16 years old to men p < 0,05), been justified by the higher experience, responsibility, especially in the case of an undesired pregnancy. As factors which predispose to precocious sexual initiation, it was mentioned: the influence of couples, of media, the beliefs and cultural norms, and the use of alcohol. In the second category, Prevention, the nonsystematic use of condom was related to the inexperience, to the existence of negative beliefs, to the unpredictability of the action, to the difficult of obtainment and access, to the lack of information and sort of affective relationship. Only 59% of the adolescents declared to have some knowledge about contraceptive methods, been highlighted the male condom (43%) and the pill (33%), and the major knowledge by the female adolescents (80%). It was described the occurrence of 195 cases of pregnancy and 75 cases of abort. The reasons which led the pregnancy in adolescents are the lack of care, difficulty in the access to the contraceptive method and the guarantee of continuation of the relationship. In the category Vulnerability to AIDS, 83% of the adolescents who had already sexual relations did not think themselves as vulnerable and 15% of the total declared not receive information concerning HIV/AIDS. As sources of information were mentioned school (59%), family (22%), media (18%), and health professionals (16%); this last source with a higher percentage to the women and in the rural area. It is concluded that the normative social speech, mainly associated to the gender roles, reveal beliefs and behaviors in this stage of life, causing more female difficulty to the prevention. It was also observed that the information passed to this population still are presented as biological and moralist, putting in evidence the necessity of interventions which comprises beliefs and norms assumed by this population.